Mutation of Gyra Gene Found In Mycobacterium Leprae From Leprosy Patient In West Papua and Papua, Indonesia - Yustinus Maladan; Hana Krismawati; Rosana Agus; Hotma M.L. Hutapea; Ratna Tanjung; Vatim Dwi Cahyani; Muhammad Fajri Rokhmad; Arli Aditya Parikesit (Universitas Gadjah Mada, 2021)
Cases of leprosy in Indonesia are still high, especially in the provinces of West Papua, North Maluku and Papua. Drug resistance surveillance and typing strains of Mycobacterium leprae are useful molecular tools for leprosy control especially in the three Provinces. The purpose of this study was to identify mutations in the gyrA          M. leprae gene obtained from leprosy patients in the provinces of West Papua and Papua on a molecular basis. M. leprae samples obtained from leprosy patients were extracted and continued with PCR and sequencing in the M. leprae gyrA gene. The sequencing results are aligned with M. leprae TN sequences to identify mutations. The phylogenetic tree was constructed using Mega 7 to get the M. leprae gyrA cluster. The RNAalifold server was employed to generate the conserved 2D structure for the gyrA MSAs. Six variants were found in the gyrA M. leprae obtained from the provinces of West Papua and Papua. The six variants are H71R, K73R, D95G, A101T, R107W, A127V. The existence of mutations in the gyrA M. leprae gene found in this study can be information in the treatment of leprosy in Papua if using Ofloxacin as an alternative treatment. Based on phylogenetic analysis found there are three distinct clusters of gyrA gene. The five variants are H71R, K73R, A101T, R107W, A127V are new variant of gyrA M. leprae. The D95G variant has been confirmed to cause resistance to Fluoroquinolone by in vitro methods, while the H71R, K73R, A101T, R107W, A127V variants are new variants whose effects on the fluoroquinolone are unknown. Thus, further analysis is needed to study the effects of the five variants on ofloxacin.